Clinical Management: Resectable Disease. Issue 6 (November 2017) - White, Rebekah R.; Lowy, Andrew M.
Abstract : Abstract: Despite the identification of more active systemic therapy combinations for pancreatic cancer, cures remain elusive and feasible only in patients with localized, operable disease. When examining outcome data from phase III adjuvant trials conducted during the past decade, the survival for patients with localized disease has improved, likely owing to a combination of factors including more active adjuvant therapy and improved surgical and perioperative care. Perhaps the greatest recent change in the care of patients with localized pancreatic cancer has been the extension of surgery to tumors previously thought to be inoperable because of involvement of major blood vessels. These so-called "borderline resectable pancreatic cancers" have now been objectively defined, and their management is being studied in randomized trials. This has been made feasible by the availability of more active systemic therapy combinations that are increasingly being used in the neoadjuvant setting. Given the increasing activity of systemic regimens, the challenges in delivering such therapy in the postoperative setting, and the numerous novel agents in late stages of clinical development, it is reasonable to hypothesize that the neoadjuvant setting may eventually become the standard of care for patients with resectable disease.